2007
DOI: 10.1002/ijc.22605
|View full text |Cite
|
Sign up to set email alerts
|

Identification of overexpressed genes in hepatocellular carcinoma, with special reference to ubiquitin‐conjugating enzyme E2C gene expression

Abstract: This study consisted of 2 aims: (i) to determine genes associated with hepatocellular carcinoma (HCC) by microarray analysis; and (ii) to evaluate the clinicopathological significance of human ubiquitin-conjugating enzyme E2C (Ube2c) found to be overexpressed in HCC from microarray analysis. Laser microdissection and cDNA-microarray were performed to identify genes associated with HCC. We then focused on the Ube2c gene. Using realtime quantitative reverse transcription-polymerase chain reaction (RT-PCR), Ube2c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
64
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 32 publications
11
64
0
Order By: Relevance
“…Another example of a gene persistently altered by the MF diet that might contribute to the development of liver dysfunction is Ubiquitin‐conjugating enzyme 2c ( Ube2c ). Ube2c has been identified as a hepatocellular carcinoma gene 81, 82 and we observed elevated expression of Ube2c already at the age of 6 months in the MF‐exposed mice (Supporting Information Fig. 3B) but the INT diet appears to reverse this effect at young age.…”
Section: Discussionmentioning
confidence: 71%
“…Another example of a gene persistently altered by the MF diet that might contribute to the development of liver dysfunction is Ubiquitin‐conjugating enzyme 2c ( Ube2c ). Ube2c has been identified as a hepatocellular carcinoma gene 81, 82 and we observed elevated expression of Ube2c already at the age of 6 months in the MF‐exposed mice (Supporting Information Fig. 3B) but the INT diet appears to reverse this effect at young age.…”
Section: Discussionmentioning
confidence: 71%
“…Our study demonstrated that siRNA-mediated suppression of UBE2C expression inhibited the growth rate of CRC cells with accumulation of cyclins A and B1, which was consistent with earlier reports. 13,16 Interestingly, we found that down-regulation of UBE2C expression caused inhibition of cell viability by arresting cells in the G2/M phase followed by induction of apoptosis in CRC cells. UBE2C expression in CRC cell lines was found to be inversely associated with cyclin A and B1 in concordance with the mechanistic model of UBE2C function.…”
Section: Discussionmentioning
confidence: 86%
“…3,6 Overexpression of UBE2C at the mRNA level has been reported in a number of cancer cell lines and primary tumors, whereas only low levels were found in normal tissues. 7 The oncogenic role of UBE2C is also reported in thyroid, 8 ovarian, 9 esopha-geal, 10 breast, 11 lung, 12 liver, 13 and brain 14 tumors. Takahashi et al 15 suggest that overexpression of UBE2C may play an important role in advanced colon cancer with liver metastases and that this overexpression may be a result of chromosomal amplification at the UBE2C locus, 20q13.1.…”
mentioning
confidence: 98%
“…Ubiquitin-conjugating enzyme E2C (UBE2C) belongs to the E2 family, and is involved in mitotic cyclin destruction and cell cycle progression (8). UBE2C has been implicated in the carcinogenesis of certain tumors (9,10), and is overexpressed in various human cancers, including breast, esophageal, colon, lung, liver and ovarian cancers (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%